Will the Islamic financial system fall into the financial crisis trap? some lessons to be learnt - Mohd Thas Thaker, Mohamed Asmy; Azam, S. M. Ferdous (2014)

(untitled)
The current global financial crisis revealed the end of the financial system which is basically derived from the capitalist system. Now the period of recession has taken place particularly among the developed countries wherein the real economic activities are severely affected due to this crisis. An alternative suggestion emerges in order to construct a new financial architecture to replace the existing financial system. In this context, the Islamic financial system can be reckoned as an effective solution for current financial crisis and alternative financial system. However, the sustainability of this system is still questionable and it will be examined critically in this study especially in terms of its possibility to fall into the financial crisis trap. This study found that the Islamic financial system might fall into the financial crisis due to its mechanism which operates within the conventional structure instead of its own structure.